A Description of The Use of Traditional Medicines For Self Medication in Hampalit Village - Nurul Qamariah; Mahdalena, Mahdalena (Jurnal EduHealth, 2024)
Self-medication is a self-medication effort using traditional medicine. Local knowledge on the use of medicinal plants in Hampalit Village is still not well documented. Local knowledge is usually only passed down orally from generation to generation. Over time, the younger generation's interest in preserving local knowledge will decrease, so that the knowledge will gradually become extinct. This study aims to obtain data in the form of plant species, parts used, and processing methods, and to find out what are the health benefits. This research was conducted with a descriptive research design, and data collection techniques using observation, interviews, and documentation. The results of this study are that there are 32 types of medicinal plants used. The most commonly used part of medicinal plants is the leaves. The most commonly used way of processing medicinal plants is by boiling. There are 24 uses for medicinal plants, namely treating high blood sugar, cancer, fever, high blood pressure, fever spasms, sciatica, acute cystitis, blood circulation, stroke, gout, lung and heart health, gray hair, as supplements, cough, vomiting blood, stomach pain, constipation, cholesterol, allergies, treating eye disorders, wounds, malaria, and helping to dissolve kidney stones.